The stability of flow velocity and intracoronary resistance in the intracoronary electrocardiogram-triggered pressure ratio - Masafumi Nakayama (Nature Portfolio, 2021)
Abstract Assessment of coronary artery lesions using the fractional flow reserve and instantaneous flow reserve (iFR) measurements has been found to reduce the incidence of further cardiovascular events. Here, we investigated differences in terms of coronary flow velocity and resistance within the analysis interval between the iFR and the intracoronary electrocardiogram (IC-ECG)-triggered distal/aortic pressure (Pd/Pa) ratio (ICE-T). We enrolled 23 consecutive patients (n = 33 stenoses) who required coronary flow measurements. ICE-T was defined as the average Pd/Pa ratio in the period corresponding to the isoelectric line of the IC-ECG. We compared the index value, flow velocity, and intracoronary resistance during the analysis intervals of the iFR and the ICE-T, both at rest and under hyperemia. ICE-T values and ICE-T intracoronary resistance were both found to be significantly lower, whereas flow velocity was significantly higher than those of the iFR at both rest and under hyperemia (P < 0.001), and all fluctuations in ICE-T values were also significantly smaller than those in the iFR. In conclusion, the ICE-T appears theoretically superior to pressure-dependent indices for analyzing phases with low and stable resistance, without an increase in invasiveness.